2009
DOI: 10.1086/648441
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal Toxic Shock Syndrome Erythroderma Is Associated with Superantigenicity and Hypersensitivity

Abstract: Staphylococcal toxic shock syndrome (TSS) has rarely been reported without rash and desquamation. This study describes a patient who met all criteria for TSS except erythroderma and desquamation. The associated staphylococcal superantigen was enterotoxin B. We demonstrate erythroderma depends on pre-existing T cell hypersensitivity amplified by superantigenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Exposure to SAgs that are either preformed (as in intentional exposure following attacks with biological weapons containing SAgs) or produced in vivo after bacterial infection can cause potent immune activation. In certain conditions, this immune activation can be robust, leading to a severe systemic cytokine storm (eg, TSS, Kawasaki disease, and neonatal TSS-like exanthematous disease 4,10,11 ). While SIRS leads to MODS and death, in the absence of prompt intervention, 3 the immunopathogenesis of this process is poorly understood because of lack of a robust animal model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to SAgs that are either preformed (as in intentional exposure following attacks with biological weapons containing SAgs) or produced in vivo after bacterial infection can cause potent immune activation. In certain conditions, this immune activation can be robust, leading to a severe systemic cytokine storm (eg, TSS, Kawasaki disease, and neonatal TSS-like exanthematous disease 4,10,11 ). While SIRS leads to MODS and death, in the absence of prompt intervention, 3 the immunopathogenesis of this process is poorly understood because of lack of a robust animal model.…”
Section: Discussionmentioning
confidence: 99%
“…033. tribute to the pathogenesis of the associated disease. [8][9][10] The severity of disease is probably determined by the quantitative and qualitative characteristics of the SAg. Toxic shock syndrome (TSS) is one of the most serious clinical syndromes caused by S. aureus and S. pyogenes and their SAgs.…”
mentioning
confidence: 99%
“…Our approach has involved the use of soluble, high-affinity receptors that could neutralize the toxins in much the same way as the TNF-␣-neutralizing agent Enbrel, a soluble form of the TNF-␣ receptor, neutralizes its target (6). Our previous success in animal models using a soluble high-affinity V␤ domain against SEB (G5-8) suggested that this approach has potential (9,21). Here, we have generated high-affinity V␤ against SpeA and explored the possible uses of V␤ agents in neutralizing multiple SAgs, such that the same drug might be used against different infectious agents.…”
Section: Discussionmentioning
confidence: 99%
“…It is now recognized that often one of the defining criteria is not present; this illness is considered probable staphylococcal TSS (99). The defining criterion most often missing is the scarlet fever-like rash that occurs in association with preexistent delayed hypersensitivity to staphylococcal superantigens (61,150). However, cases of probable TSS in which each defining criterion has been absent have been described.…”
Section: Staphylococcal Menstrual Tssmentioning
confidence: 99%